Identification of the Common Origins of Osteoclasts, Macrophages, and Dendritic Cells in Human Hematopoiesis - Xiao, Yanling (Stem Cell Reports, 2015)
Osteoclasts (OCs) originate from the myeloid cell lineage, but the successive steps in their lineage commitment are ill-defined, especially in humans. To clarify OC origin, we sorted cell populations from pediatric bone marrow (BM) by flow cytometry and assessed their differentiation potential in vitro. Within the CD11b(−)CD34(+)c-KIT(+) BM cell population, OC-differentiation potential was restricted to FLT3(+) cells and enriched in an IL3 receptor (R)α(high) subset that constituted less than 0.5% of total BM. These IL3Rα(high) cells also generated macrophages (MΦs) and dendritic cells (DCs) but lacked granulocyte (GR)-differentiation potential, as demonstrated at the clonal level. The IL3Rα(low) subset was re-defined as common progenitor of GR, MΦ, OC, and DC (GMODP) and gave rise to the IL3Rα(high) subset that was identified as common progenitor of MΦ, OC, and DC (MODP). Unbiased transcriptome analysis of CD11b(−)CD34(+)c-KIT(+)FLT3(+) IL3Rα(low) and IL3Rα(high) subsets corroborated our definitions of the GMODP and MODP and their developmental relationship.